Cigarette Taxes, Smoking, and Health in the Long Run - Andrew Friedson; Moyan Li; Katherine Meckel; Daniel I. Rees; Daniel W. Sacks (Center for Economic Studies and ifo Institute (CESifo), 2021)
Medical experts have argued forcefully that using cigarettes harms health, prompting the adoption of myriad anti-smoking policies. The association between smoking and mortality may, however, be driven by unobserved factors, making it difficult to discern the underlying long-term causal relationship. In this study, we explore the effects of cigarette taxes experienced as a teenager, which are arguably exogenous, on adult smoking participation and mortality. A one-dollar increase in teenage cigarette taxes is associated with an 8 percent reduction in adult smoking participation and a 6 percent reduction in mortality. Mortality effects are most pronounced for heart disease and lung cancer.
Keywords: H20; I10; I12; 330; smoking; cigarette taxes; mortality